APPLICATION OF THE VIBRATIONALLY ADIABATIC AND STATIC DISTORTED-WAVE BORN APPROXIMATIONS TO THE REACTION H+F2(NU=0,J=0)-]HF(NU',J')+F - Clary, D; Connor, J (1979)
Relative vibration-rotation reaction probabilities for the H + F2(ν = 0,j = 0) → HF(ν′,j′) + F reaction on the best extended LEPS potential energy surface No. II of Jonathan et al. have been computed using a three-dimensional, quantum-dynamical, distorted-wave Born approximation. Good agreement with experimental, quasiclassical trajectory, and collinear quantum results has been obtained provided the vibrational wavefunction of F2 is allowed to distort adiabatically as the II atom approaches, and is not held static. © 1979.